A randomized prospective comparison of the Baxter and Modified Brooke formulas for acute burn resuscitation. Issue 3 (July 2021) - Saitoh, Daizoh; Gando, Satoshi; Maekawa, Kunihiko; Sasaki, Junichi; Fujishima, Seitaro; Ikeda, Hiroto; Shiino, Yasukazu; Takuma, Kiyotsugu; Nakada, Taka-aki; Tanaka, Katsumi; Tasaki, Osamu; Nemoto, Manabu; et al.
Highlights: Comparing between the Modified Brooke and Baxter formulas. There were no significant differences between the 2 groups at 24 h after major burns. The initial lack of urine in patients was not found to be a clinical problem. Abstract: Background: Starting infusion at a rate based on the Baxter formula is the global standard. However, with this infusion formula, an excessive amount of fluid may be stored inside the body (fluid creep), which may lead to severe respiratory disorders or abdominal compartment syndrome. The present study explored whether the Baxter formula or the Modified Brooke formula is more beneficial for resuscitation in extensively burned patients. Methods: The study design was a randomized controlled trial. One group received conventional intervention based on the Baxter formula, and the other received intervention using the infusion method by the Modified Brooke formula. Thirty-nine patients were enrolled in this study by admission to each hospital for 3 years. Of the 39 cases, 3 dropped out according to the study protocol, so 36 cases were analyzed, and 17 patients in the Modified Brooke formula group and 19 in the Baxter formula group were used for the analyses in this study. Results: There were no statistically significant differences between the 2 groups in the age, gender, body weight, burn severity, infusion volume required within 2 days after admission, serum creatinine, and acute kidney injury based on the KDIGO guideline within 48 h after arrival at the hospital, daily P/F ratio within 1 week after hospitalization, survival rate on the 28th day, and discharge survival rate. There were no cases of abdominal compartment syndrome during the observation period. The Modified Brooke formula group failed to achieve the target urine output corresponding to the infusion volume within 8 h after arrival, especially in ≥40% TBSA burn patients, but it did not become a clinical problem. Conclusion: We were unable to conclusively demonstrate that the Modified Brooke formula blocked the occurrence of "fluid creep" in extensively burned patients. However, it was suggested that starting the initial resuscitation at half the conventional volume might contribute to an improved physiological condition in the acute phase of major burns.